Mechanical properties of a new fully prefabricated staggered flip-down slab - Ruan, Xuanqi; Chen, Deshen; Zhang, Yan; He, Zimeng; Li, Yaning; An, Baiping (Journal of Civil Engineering and Management, 2023)
Prefabricated slab has been widely used in the global construction industry due to energy saving, environmental protection, and good economic advantages. In this paper, a new type of fully prefabricated staggered flip-down slab without cast-in-situ operation has been proposed. First, the experiments were carried out on the new slab. The structural performance of the new slab was compared with the cast-in-situ slabs and composite slabs of the same specification. The experimental results showed that the ultimate bearing capacity of the new slab meets the requirements for practical utilization. On this basis, an additional CFRP sheet could be pasted on the bottom initial seam between prefabricated slabs to enhance the integrity and prevent cracks. Then, the whole loading process of the slab was simulated, and the results were consistent with the experimental results. Finally, through experiments and parametric analysis, recommendations for improvement were put forward to enhance the mechanical properties of this kind of slab.